Analisis Perkembangan Pembangkit Listrik Tenaga Bayu (PLTB) Sebagai Sumber Energi Alternatif Terbarukan Di Indonesia - Wulandari, Jennis Ayu; ., Sudarti; ., Yushardi (Jurnal Pendidikan, Sains Dan Teknologi, 2023)
One of the government's steps in the energy sector is to immediately develop and introduce renewable energy sources to reduce dependence on fossil fuels. Supporting government policies regarding community energy supply, including wind energy, requires the introduction of the use of new renewable energy sources based on local potential. To support this government program, non-profit programs are being implemented in several cities in Indonesia to exploit the potential of wind energy. Wind speed, or the average wind energy that can be harvested each day, on Mount Kinshiel ranges from 60.14 to 77.59 W per hour. On the other hand, wind speed in Gresik Regency has been unstable for 10 days, with an average wind speed of 1.5 m/s and wind strength of 10.47 watts during those 10 days. In Palu City, the PLTB electricity generation capacity is 28,308 kWh/day, and the 900 VA electricity supply from the PLTB system is distributed to approximately 31 houses (electricity consumers).